(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
This study examines the effects of inflation on jewelry consumers in Nepalgunj, Nepal, using a descriptive research design. The research aims to understand how inflation affects purchasing power, identify coping strategies, assess the impact on demand, and explore mitigation measures. The findings reveal that 70% of respondents believe middle-class individuals are most affected by inflation, leading to reduced jewelry affordability. Additionally, 30% of respondents agree that people buy less jewelry nowadays, and 76% agree that customers opt for substitute products as gifts instead of jewelry. The study suggests that inflation significantly impacts the jewelry industry, reducing consumer purchasing power and altering spending behaviors. To navigate these challenges, businesses in the jewelry sector must adopt strategic measures, such as price adjustments, value emphasis, and efficient sourcing practices. The findings provide valuable insights for policymakers, economists, and businesses in the jewelry industry. The study’s implications include the need for policymakers toconsider the impact of inflation on the jewelry industry and its consumers, for economists to develop models that better predict consumer behavior during inflation, and for businesses to adopt strategic measures to mitigate the effects of inflation. Overall, the study highlights the importance of understanding the effects of inflation on jewelry consumers and the need for stakeholders to take proactive measures to address these challenges.